2022
DOI: 10.3390/plants11111475
|View full text |Cite
|
Sign up to set email alerts
|

Brachypodium Antifreeze Protein Gene Products Inhibit Ice Recrystallisation, Attenuate Ice Nucleation, and Reduce Immune Response

Abstract: Antifreeze proteins (AFPs) from the model crop, Brachypodium distachyon, allow freeze survival and attenuate pathogen-mediated ice nucleation. Intriguingly, Brachypodium AFP genes encode two proteins, an autonomous AFP and a leucine-rich repeat (LRR). We present structural models which indicate that ice-binding motifs on the ~13 kDa AFPs can “spoil” nucleating arrays on the ~120 kDa bacterial ice nucleating proteins used to form ice at high sub-zero temperatures. These models are consistent with the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Several cold-induced genes, including AmCIP [10], AmLEA, AmEBP1 [11], and AmCaM [12], have been isolated and functionally characterized via ectopic expression. In addition, several antifreeze proteins proposed to contribute to the freezing tolerance of A. mongolicus have been purified, and their antifreeze activities have been determined [13,14]. These studies demonstrate the efficacy of using A. mongolicus to identify cold stress tolerance-related genes.…”
Section: Introductionmentioning
confidence: 89%
“…Several cold-induced genes, including AmCIP [10], AmLEA, AmEBP1 [11], and AmCaM [12], have been isolated and functionally characterized via ectopic expression. In addition, several antifreeze proteins proposed to contribute to the freezing tolerance of A. mongolicus have been purified, and their antifreeze activities have been determined [13,14]. These studies demonstrate the efficacy of using A. mongolicus to identify cold stress tolerance-related genes.…”
Section: Introductionmentioning
confidence: 89%
“…It has also been shown that INP activity is affected by pH, which is consistent with a role for electrostatic interactions (19). We and others have suggested that INPs may multimerize through salt-bridging of the sidechains in these positions of the coil (8, 20).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that INP activity is affected by pH, which is consistent with a role for electrostatic interactions ( Schwidetzky et al, 2021 ). We and others have suggested that INPs may multimerize through salt-bridging of the side chains in these positions of the coil ( Forbes et al, 2022 ; Juurakko et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%